Women's lives, men's laws - MacKinnon, Catharine A. (Belknap Press of Harvard Univ. Press, 2005)
In the past twenty-five years, no one has been more instrumental than Catherine MacKinnon in making equal rights real for women. As Peter Jennings once put it, more than anyone else in legal studies, she "has made it easier for other women to seek justice". This collection brings together previously uncollected and unpublished work in the national arena from 1980 to the present, defining her clear, coherent, consistent approach to reframing the law of men on the basis of the lives of women. (Quelle: Text Verlagseinband / Verlag)